Federal Workers' Compensation Programs: Department of Defense and Veterans Health Administration Experiences. (March 2015) - Mallon, Timothy M.; Grizzell, Tifani L.; Hodgson, Michael J.
Abstract : Objective: The objective of this article is to introduce the reader to this special supplement to the Journal of Occupational and Environmental Medicine regarding Federal Workers' Compensation Programs. Methods: The short history of both the VHA and DoD Federal Workers' Compensation Programs are provided and a short synopsis of each author's article is provided. Results: The lessons learned from the articles in the supplement are summarized in this article and 6 key findings are highlighted. Conclusions: Cooperation between human resources workers' compensation personnel, safety and occupational health personnel is a must for successful management of the WC program. Information and data sharing are critical for root cause and injury prevention, case management, and cost containment efforts. Enhancing efforts in these areas will save an estimated $100 million through cost avoidance efforts.